Using Raw Material Flow Cost Accounting to Reduce Production Spoilage - Hamza Ghaly, Zina (Iraqi Journal for Administrative Sciences, 2021)
Improving environmental performance is an urgent need for all companies that have shifted focus from obsessing with short-term profits to thinking of long-term strategies to achieve sustainable management. Material flow cost accounting (MFCA) is an environmental management tool that can balance the environment and the economy. The research aims to achieve a balance between the financial and environmental dimensions through the use of statistical methods and to identify the level of perception of the company, the research sample for the technique of accounting for material flow costs, as well as knowing the nature of the relationship between accounting for material flow costs and reducing production spoilage and its impact on environmental pollution, and in order to achieve the research objectives, the approach was used. Descriptive and analytical to obtain data related to the theoretical aspect, and a survey questionnaire was used to collect primary data related to the topic of the research, which was distributed to employees of textile laboratories and bridges in Dhi Qar. As well as working on the technical and administrative skills of workers in dealing with the concept of environmental pollution by using environmentally friendly raw materials.